2009
DOI: 10.1111/j.1365-2761.2009.01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Artemia franciscana (Kellogg) larvae with bacterial heat shock protein, protects from Vibrio campbellii infection

Abstract: Among their numerous physiological effects, heat shock proteins (Hsps) are potent immunomodulators, a characteristic reflecting their potential as therapeutic agents and which led to their application in combating infection. As an example, the up-regulation of endogenous Hsp70 in the branchiopod crustacean Artemia franciscana (Kellogg) is concurrent with shielding against bacterial infection. To better understand this protective mechanism, gnotobiotic Artemia were fed with Escherichia coli treated to over-prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 59 publications
(77 reference statements)
0
34
0
Order By: Relevance
“…Additionally, immunoprobing of Western blots and protein quantification by ELISA demonstrated that enhanced protection is associated with increased DnaK accumulation in bacteria used as feed. Previously, feeding with E. coli overexpressing DnaK, produced under the control of either its own promoter or a heterologous arabinose-inducible promoter, boosted Artemia survival approximately threefold (Sung et al 2009). The present study extends these observations, demonstrating clearly that DnaK-producing bacteria other than E. coli confer protection upon Artemia larvae.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, immunoprobing of Western blots and protein quantification by ELISA demonstrated that enhanced protection is associated with increased DnaK accumulation in bacteria used as feed. Previously, feeding with E. coli overexpressing DnaK, produced under the control of either its own promoter or a heterologous arabinose-inducible promoter, boosted Artemia survival approximately threefold (Sung et al 2009). The present study extends these observations, demonstrating clearly that DnaK-producing bacteria other than E. coli confer protection upon Artemia larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Protein extraction was as described (Sung et al 2009). Bacteria were homogenized in the presence of 0.1 mm diameter glass beads in ice-cold buffer K (150 mM sorbitol, 70 mM potassium gluconate, 5 mM MgCl 2 , 5 mM NaH 2 PO 4 , 40 mM HEPES, pH 7.4) (Clegg et al 2000a) containing protease inhibitors (catalog no.…”
Section: Immunodetection Of Hspsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hsp70 has a role in the growth of A. franciscana (Clegg et al 2000;Willsie and Clegg 2002) and protection against stress, including heat and pathogenic bacteria (Sung et al 2008(Sung et al , 2009aBaruah et al 2011), but information on its major co-chaperone, Hsp40, is lacking as it is for most crustaceans. With this in mind, a search was initiated for J-domain proteins in A. franciscana resulting in the cloning and sequencing of a complementary DNA (cDNA), termed ArHsp40, encoding a type I Hsp40.…”
Section: Introductionmentioning
confidence: 99%